PENGARUH CORPORATE SOCIAL RESPONSBILITY TERHADAP FINANCIAL DISTRESS DIMODERASI OLEH SIKLUS HIDUP PERUSAHAAN PADA TAHAP MATURE - Retno Wati Purwaningsih; Nurna Aziza (Jurnal Akuntansi, 2019)
This research investigated to prove that corporate social responsibility has a negative effect on financial distress, and the firm life cycle at the mature stage strengthen effect of corporate social responsbility on financial distress. The populations of this study were all manufacturing companies listed on the Indonesia Stock Exchange during the years 2014-2017. Methods of data collection used purposive sampling techniques. There were 49 companies with 170 observations that fulfilled the criteria to be the study sample. This study uses a quantitative approach. Data were analyzed using logistic regression and moderated regression analysis (MRA) with the help of SPSS software. The result showed that corporate social responsibility has a negative effect on financial distress, the firm life cycle at the mature stage strengthens the effect of corporate social responsibility on financial distress. Keywords: Corporate social responsibility, Financial distress, Firm life cycle at the mature stage